The Wegener's granulomatosis quantitative trait locus on chromosome 6p21.3 as characterised by tagSNP genotyping. Issue 7 (29th October 2007) - Heckmann, M; Holle, J U; Arning, L; Knaup, S; Hellmich, B; Nothnagel, M; Jagiello, P; Gross, W L; Epplen, J T; Wieczorek, S
Abstract : Background: A genomic region on chromosome 6p21.3, including HLA-DPB1, has been linked to Wegener's granulomatosis (WG). The basis of this association is difficult to evaluate because of the complex haplotype block architecture of this region. Objective: To identify the causative molecular genetic variation(s) using a detailed HapMap based fine-mapping approach. Methods: 282 patients with WG and 380 healthy controls were genotyped for HLA-DPB1 as well as for 35 informative single nucleotide polymorphisms (SNPs) within the respective region. 25 of these SNPs have been selected as tagging SNPs for another 219 associated SNPs. Allele and genotype frequencies were analysed separately by contingency tables and logistic regression. Finally, the coding region of RING1 was directly sequenced in subjects who carried haplotypes that were correlated with contrasting WG risks. Results: The previously reported strong association of WG with the HLA-DPB1*0401 allele was confirmed in an independent WG sample (n = 108, pc = 6.4×10 −8 ). When the complete cohort (n = 282) was considered, the association remained highly significant in ANCA-positive (pc = 1.26×10 −22 ), but not in ANCA-negative patients. An SNP 3′ of HLA-DPB1 yielded the smallest p value and was associated with WG partly independently from the HLA-DPB1 alleles. Another informative SNP in the vicinity of RING1 showed significant WG association that was also partly independent of HLA-DPB1. RING1 sequencing, however, did not show any variation potentially predisposing to WG. Conclusions: The HLA-DPB1/RING1 region is strongly associated with WG in ANCA-positive subjects. Further analyses of potential cis regulatory sequences of candidate genes HLA-DPB1, RING1 and RXRB appear warranted.